Thinking about biology - Webster, Stephen 1957- (Cambridge University Press, 2003)
Thinking about Biology is intended for biology students who are interested in reflecting on the wider contexts of their studies. This 2003 book encourages students to see that biology does not deliver certainties; it discusses how biological ideas become established facts; it uses history to examine how ideas change, and to show that the biological facts that form the basis of a biology course are likely to change too. Each chapter is based on biological topics, and examines them for their philosophical, social and political implications. Topics covered include the role of natural selection in evolution, the history of ideas about fertilisation and inheritance, vivisection, and reductionism. Genetically modified foods, xenotransplantation, eugenics, and genetic testing are some of the controversial subjects discussed. Thinking About Biology should be essential reading for all college students already taking a biology course, and for those contemplating such a course in the future.